MODERNIZATION OF ISLAMIC EDUCATION A Network Study of Integrated Islamic Schools in North Sumatra - Wahdi, Wahdi; Asari, Hasan; Arsyad, Junaidi (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
This paper explains the modernization of Islamic education through a case study of the Integrated Islamic School Network (JSIT) in North Sumatra. The shifting educational landscape and the rising demands of a globalized society propel the need for modernizing Islamic education in Indonesia. Traditional Islamic educational institutions like madrasahs and pesantren are complemented by integrated Islamic schools that balance religious teachings with contemporary academic knowledge. This transformation addresses the educational needs of Indonesia's large Muslim population while preserving Islamic values and identity. The emergence of these integrated schools indicates a significant shift towards a more holistic educational approach that includes both Islamic and secular curricula, reflecting the dual demand for spiritual guidance and competitive academic performance. This study explores the impact of the modernization of Islamic education through a network of Integrated Islamic Schools in North Sumatra, Indonesia. It investigates how these schools integrate traditional Islamic values with modern educational practices and how this affects educational outcomes and community perception. Employing a qualitative research design with a phenomenological approach, the study gathers in-depth descriptive data through interviews, participatory observation, and document analysis from multiple Integrated Islamic Schools. This method provides a comprehensive understanding of the educational transformations and their implications on students and educators. The results showed that JSIT North Sumatra has implemented various educational innovations, including using technology in learning, an integrated curriculum, and participatory teaching methods. This modernization process improves the quality of education in general and strengthens the integration of Islamic values in the curriculum and school activities. This study provides insights into how Islamic education can evolve to meet the needs of modern times without losing its Islamic essence.